The prevalence r ate of human herpes viruses among different age populations - S. G. Mardanly (Журнал микробиологии, эпидемиологии и иммунобиологии, 2019)
Aim. To evaluate infection with both individual types of HHV and their combinations for two categories of population — children and elderly persons. Materials and methods. The presence of IgG to human herpes viruses 1-6 and 8 types in sera of children  aged 0-18 (1006 individuals) and elderly patients  aged 60-99 (1004 individuals) was investigated by ELISA-method. Results. It was shown that 45 — 61,3% of examined children (aged 0-2 years) are infected with HHV-1, HHV-3, HHV-4, HHV-5 and HHV-6. The subsequent dynamics of infection with the first, third and fourth types of HHV expressed in the final constant growth up to 16-18 years was noted. There was no connection between children age and HHV-2, HHV-6 and HHV-8, it was ranged from 45 to 68% for HHV-6  and did not rise above 3.5 and 10% for HHV-2  and HHV-8 respectively. In most cases elderly persons of all age groups were infected with HHV-1, HHV-3, HHV-4 and HHV-5, antibodies to HHV-2 were detected in 21,3-26,6% of all individuals of this age. Conclusion. In order to ensure effective planning and implementation of adequate  treatment and preventive measures that will minimize the adverse medical and social consequences of HHV spread among the population of the Russian Federation, it is necessary to continue detailed study of HHV infection in all population groups.